Citrus aurantium L. polymethoxyflavones promote thermogenesis of brown and white adipose tissue in high-fat diet induced C57BL/6J mice. (April 2020) - Kou, Guangning; Hu, Yan; Jiang, Zixiao; Li, Zhenqing; Li, Peiyuan; Song, Hongjie; Chen, Qiyang; Zhou, Zhiqin; Lyu, Quanjun
Graphical abstract: Highlights: Dietary citrus polymethoxyflavones markedly reduced body weight gain in high-fat diet-fed mice. Dietary citrus polymethoxyflavones enhanced the activity of BAT in high-fat diet-fed mice. Citrus polymethoxyflavones promoted the iWAT browning, but not in eWAT. Citrus polymethoxyflavones activated AMPK/PGC1α signaling axis both in BAT and iWAT. Abstract: Promoting thermogenesis of brown and beige adipocytes increases energy expenditure, which is a critical approach to prevent obesity. In the present study, we elucidated the effect of the citrus polymethoxyflavones on adaptive thermogenesis in high fat diet induced obesity mouse model. The PMFs from Citrus aurantium L. analyzed by UPLC are mainly nobiletin, tangeretin and sinensetin. Dietary supplementation of 0.2% citrus PMFs with high fat diet (w/w) for 12 weeks markedly reduced body weight gain, white adipose weight and size. The cold tolerance test showed that PMFs supplementation maintained body temperature and elevated nonshivering thermogenesis. The Q-PCR and IHC revealed that PMFs promote expression of thermogenesis genes and mitochondrial biogenesis of BAT and iWAT. Mechanistically, we found that PMFs activated AMPK/PGC1α signaling axis. This study demonstrated that citrus PMFs could prevent obesity by activating thermogenesis of BAT and iWAT. PMFs may use as a novel dietary supplemental approach for obesity.